An unknown world in the Neotropical region: a complete life cycle of a new species of Monoclona Mik, 1886 (Diptera: Mycetophilidae: Sciophilinae) - Amaral, Edna Maria; Oliveira, Sarah Siqueira; Falaschi, Rafaela Lopes (Zootaxa, 2022)
Popularly known as fungus gnats, Mycetophilidae are found in humid environments usually associated with mushrooms and decaying wood. Their immature forms often feed on fungus fruiting bodies. Similar to most bibionomorphans, mycetophilids need due attention concerning their taxonomy and information on their natural history, especially in the Neotropical region. This work describes Monoclona carambeiensis sp. nov., a new species of Monoclona Mik, and furnishes information on the morphology of adults and immatures, besides notes and photographs on the life cycle of the species. Immature forms present on a piece of decaying wood with lichens and fungi were collected from Carambeí, Paraná, and reared in the laboratory. The emerged adult male was fixed in 80% ethanol. This is the first study describing an immature of a Neotropical species of Monoclona, and also the first record of the genus in the state of Paraná, Brazil. This is the third Neotropical species of Mycetophilidae to have its life cycle described, for a fauna with over 1,100 known species.